Collocations workbook: a corpus-based online pedagogical support material for the teaching of English collocations - Orenha-Ottaiano, Adriane [UNESP] (Univ Federal Minas Gerais, Fac Letras, 2015)
This study argues that the selection of collocations should be geared to targeting L2 learners of a particular L1 background and thus teaching material should be designed with a careful selection of collocations focusing on their specific difficulties (MACKIN, 1978). Bearing that in mind, this article aims at discussing the compilation of an online corpus-based collocational workbook, in order to allow English as a foreign language teachers to work with the collocations in the classroom more effectively and help learners use them more accurately and productively. Our public audience is also learner and professional translators, mainly the ones whose L1 is Portuguese. The activities are being developed based on the difficulties the Brazilian learners had regarding the use of collocations, raised from the translations carried out by university students in the Portuguese-English direction, which comprise a Translation Learner Corpus, as well as essays also written by university students which constitute a Learner Corpus. For extracting the data, the computing program WordSmith Tools (SCOTT, 2008) is used, enabling us to raise the most frequent collocational patterns employed by the learners. We also check frequency and recurrence of collocational patterns extracted as well as raise more collocations to be included in the workbook on The Corpus of Contemporary American English (DAVIES, 1990-2012). The proposal of designing an online workbook has the objective of contributing to Brazilian students' awareness of collocational aspects and mainly to the improvement of fluency in English.
Keywords: workbook; collocations corpus; pedagogical material; teaching collocations